Pemanfaatan SIG untuk Analisis Kerentanan Kerusakan Jalan di Kabupaten Grobogan - Bagus, Santoso; Suharini, Erni; Hariyanto, Hariyanto (Geo-Image, 2019)
The purpose of this research to know the degree of vulnerability of the province road damage in Grobogan Regency and to know the factor wich the most influential about vulnerability of the province road damage in Grobogan Regency. All of the province road in the area of Grobogan Regency in this research aggregate 11 roads The data collection technique used observation and documentation. The analysis data technique used SIG analysis. The result of research show from the length totally 156,23 Km, the road included in the degree vulnerability of damage to low road were 18,9 Km, middle degree 136,83 Km, and high degree 0,5 Km. The factor wich most influential toward vulnerability was traffic volume amount 30%.